Legumes in forage research programmes for smallscale livestock producers - Lazier, John R. (International Livestock Centre for Africa, 1987)
Describes some of the important methods of legume introduction into farming systems. Lists some of the legumes identified by ILCA as being of potential value. Summarises the promising genera, their environments of adaptation and their areas of usefulness.